Analysis of the Musyarokah Mutanaqisoh Contract in the Book of Fathul Qorib on BSI Kc Banyuwangi Basuki Rahmat Online Mitraguna Financing Products - Salsa Elvira; Lely Ana Ferawati Ekaningsih; Imam Muslih (SAINTIS Publishing, 2025)
The purpose of this study is to analyze the musyarokah mutanaqisoh contract in the book of fathul qorib in mitraguna financing implemented by Bank Syariah Indonesia (BSI) KC Banyuwangi Basuki Rahmat. Mitraguna Financing products use the Mutanaqisoh musyarokah contract, where mitraguna financing is a financing service that can be used for a variety of needs (multipurpose) that are halal, with a source of payment from salary income/permanent employee income (payroll through BSI). The research method used is qualitative descriptive, with data collection techniques through interviews, observations, and documentation studies. The results of the study show that BSI's online mitraguna financing makes it easy for customers to have access because it is available in the mobile banking application owned by BSI. This product offers multipurpose financing by not using collateral against assets owned by customers. The implication of this research is the importance of educating customers regarding the advantages and procedures of online mitraguna financing through the BSI mobile banking application. This research also suggests BSI to be more active in educating customers about this product so that they can understand online mitraguna financing easily.